2014
DOI: 10.1590/s0100-29452014000500002
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnology applied to Annona species: a review

Abstract: Annonaceae is an ancient family of plants including approximately 50 genera growing worldwide in a quite restricted area with specific agroclimatic requirements. Only few species of this family has been cultivated and exploited commercially and most of them belonging to the genus Annona such as A. muricata, A. squamosa, the hybrid A. cherimola x A. squamosa and specially Annona cherimola: the cherimoya, commercially cultivated in Spain, Chile, California, Florida, México, Australia, Ecuador, Peru, Brazil, New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…In vitro tissue culture (micropropagation) is among propagation methods successfully applied to species such as A. cherimola. Advances in this area are presented in a recent literature review by Encina et al (2014), who reported micropropagation with juvenile A. muricata material and protocol for micropropagation of adult A. cherimola genotypes. The authors also presented several in vitro methodologies, such as adventitious organogenesis and regeneration of cell cultures; manipulation of the 'ploidy' of A. cherimola to obtain haploid, tetraploid, triploid (seedless) plants; genetic transformation with introduction of genes aiming to control the post-harvest processes and to provide resistance to pathogens and insects; and micropropagation and regeneration of other wild species of the genus Annona, such as A. senegalensis, A. scleroderma, A. montana, among others.…”
Section: In Vitro Tissue Culturementioning
confidence: 99%
“…In vitro tissue culture (micropropagation) is among propagation methods successfully applied to species such as A. cherimola. Advances in this area are presented in a recent literature review by Encina et al (2014), who reported micropropagation with juvenile A. muricata material and protocol for micropropagation of adult A. cherimola genotypes. The authors also presented several in vitro methodologies, such as adventitious organogenesis and regeneration of cell cultures; manipulation of the 'ploidy' of A. cherimola to obtain haploid, tetraploid, triploid (seedless) plants; genetic transformation with introduction of genes aiming to control the post-harvest processes and to provide resistance to pathogens and insects; and micropropagation and regeneration of other wild species of the genus Annona, such as A. senegalensis, A. scleroderma, A. montana, among others.…”
Section: In Vitro Tissue Culturementioning
confidence: 99%
“…x Annona squamosa L.) and soursop (Annona muricata L.) have dramatically increased and many issues of incompatibility have been observed in the field. In orchards, Annonaceae species of economic importance are grafted to ensure that the genetic characteristics of productive scions are maintained (Almeida et al 2010;Encina et al 2014), however, graft incompatibility is frequently observed. Graft incompatibility is generally Communicated by LA Kleczkowski. & Daniel Baron agroozzy@yahoo.com.br; danielbaron.agro@gmail.com defined as the interruption in cambial and vascular continuity between rootstock and scion (Hartmann et al 2011;Kostopoulou and Therios 2014;Li et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Trabalhos que abordem a micropropagação do gênero Xylopia não são reportados na literatura. No entanto, para a família Annonaceae, principalmente para o gênero Annona, a possibilidade de uso da micropropagação tem sido investigada com o intuito de contornar problemas em relação à propagação por métodos convencionais (Encina et al, 2014).…”
Section: Discussionunclassified